Bacterial endophyte Sphingomonas sp. LK11 produces gibberellins and IAA and promotes tomato plant growth - Khan, Abdul Latif; Waqas, Muhammad; Kang, Sang-Mo; Al-Harrasi, Ahmed; Hussain, Javid; Al-Rawahi, Ahmed; Al-Khiziri, Salima; Ullah, Ihsan; Ali, Liaqat; Jung, Hee-Young; Lee, In-Jung (The journal of microbiology, 2014)
Plant growth promoting endophytic bacteria have been identified as potential growth regulators of crops. Endophytic bacterium, Sphingomonas sp. LK11, was isolated from the leaves of Tephrosia apollinea. The pure culture of Sphingomonas sp. LK11 was subjected to advance chromatographic and spectroscopic techniques to extract and isolate gibberellins (GAs). Deuterated standards of [17, 17-²H₂]-GA₄, [17, 17-²H₂]-GA₉ and [17, 17-²H₂]-GA₂₀ were used to quantify the bacterial GAs. The analysis of the culture broth of Sphingomonas sp. LK11 revealed the existence of physiologically active gibberellins (GA₄: 2.97 ± 0.11 ng/ml) and inactive GA₉ (0.98 ± 0.15 ng/ml) and GA₂₀ (2.41 ± 0.23). The endophyte also produced indole acetic acid (11.23 ± 0.93 μM/ml). Tomato plants inoculated with endophytic Sphingomonas sp. LK11 showed significantly increased growth attributes (shoot length, chlorophyll contents, shoot, and root dry weights) compared to the control. This indicated that such phyto-hormones-producing strains could help in increasing crop growth.